Distinct Roles of TRAPPC8 and TRAPPC12 in Ciliogenesis via Their Interactions With OFD1 - Zhang, Caiyun; Li, Chunman; Siu, Gavin Ka Yu; Luo, Xiaomin; Yu, Sidney (Frontiers in Cell and Developmental Biology, 2020)
The transport protein particle (TRAPP) complex was initially identified as a tethering factor for COPII vesicle. Subsequently, three forms (TRAPPI, II, and III) have been found and TRAPPIII has been reported to serve as a regulator in autophagy. This study investigates a new role of mammalian TRAPPIII in ciliogenesis. We found a ciliopathy protein, oral-facial-digital syndrome 1 (OFD1), interacting with the TRAPPIII-specific subunits TRAPPC8 and TRAPPC12. TRAPPC8 is necessary for the association of OFD1 with pericentriolar material 1 (PCM1). Its depletion reduces the extent of colocalized signals between OFD1 and PCM1, but does not compromise the structural integrity of centriolar satellites. The interaction between TRAPPC8 and OFD1 inhibits that between OFD1 and TRAPPC12, suggesting different roles of TRAPPIII-specific subunits in ciliogenesis and explaining the differences in cilium lengths in TRAPPC8-depleted and TRAPPC12-depleted hTERT-RPE1 cells. On the other hand, TRAPPC12 depletion causes increased ciliary length because TRAPPC12 is required for the disassembly of primary cilia. Overall, this study has revealed different roles of TRAPPC8 and TRAPPC12 in the assembly of centriolar satellites and demonstrated a possible tethering role of TRAPPIII during ciliogenesis.